Diagnostic performance of patient self‐collected oral swab (tongue and cheek) in comparison with healthcare worker‐collected nasopharyngeal swab for severe acute respiratory syndrome coronavirus‐2 detection. Issue 11 (8th September 2022) - Mane, Arati; Jain, Shilpa; Jain, Ankita; Nema, Vijay; Kurle, Swarali; Saxena, Vandana; Pereira, Michael; Sirsat, Atul; Pathak, Gaurav; Bhoi, Vikalp; Bhavsar, Shailaja; Panda, Samiran
Abstract : The present study was conducted to compare the performance of patient self‐collected oral swab (OS) with healthcare worker (HCW)‐collected nasopharyngeal swab (NPS) for SARS‐CoV‐2 detection by reverse transcription polymerase chain reaction (RT‐PCR) in real‐world setting. Paired OS and NPS were collected from 485 consecutive individuals presenting with symptoms of coronavirus disease‐19 (COVID‐19) or asymptomatic contacts of COVID‐19 cases. Both specimens were processed for RT‐PCR and cycle threshold (Ct) value for each test was obtained. Positive percent agreement (PPA), negative percent agreement (NPA), overall percent agreement (OPA) and kappa were calculated for OS RT‐PCR compared with NPS RT‐PCR as reference. A total of 116/485 (23.9%) participants were positive by NPS RT‐PCR. OS had PPA of 71.6%, NPA of 98.8%, OPA of 92.4% and kappa of 0.771. Almost all participants (483/485, 99.6%) reported OS as a convenient and comfortable sample for SARS‐CoV‐2 testing over NPS. All participants with Ct values <25 and majority (90.8%) with Ct values <30 were detected by OS. To conclude, OS self‐sampling was preferred in comparison with NPS due the ease and comfort during collection. The performance of OS RT‐PCR for SARS‐CoV‐2 detection, however, was sub‐optimal in comparison with NPS RT‐PCR.